EYE RADIATION DOSE SAVING IN HEAD CT EXAMINATIONS USING COPPER-BISMUTH RADIATION SHIELD. Issue 2 (9th December 2022) - Keshtkar, Mohammad; Blouri, Basir; Mahmoudabadi, Alireza; Alami, Ali
Abstract: The aim of the present study is to fabricate a new shield with an optimal combination of copper and bismuth to protect the eyes in the head computed tomography (CT) examinations without compromising image quality. Radiation shields with different compositions were constructed. Computed Tomography Dose Index phantom was used to evaluate the effectiveness of shields in dose reduction and their impact on image quality quantitatively. The shield that caused the least noise in the phantom study was selected for human study. The 10%Bi-90%Cu shield had the least effect on increasing the image noise, and also no remarkable artifact was seen in the CT image of the phantom. The patient study showed that only in 25% of the study group the artifact was observed so that it did not distort the interpretation of the image. It can be concluded that the 10%Bi-90%Cu shield is flexible and durable and would be safely used in the clinic to reduce the eye radiation dose in head CT imaging without compromising image quality.